1981
DOI: 10.1172/jci110239
|View full text |Cite
|
Sign up to set email alerts
|

Early Recovery of Regional Performance in Salvaged Ischemic Myocardium following Coronary Artery Occlusion in the Dog

Abstract: A B S T R A C T Although numerous agents have been shown experimentally to protect ischemic myocardium, a critical unanswered question is whether function is preserved in the salvaged tissue. Accordingly, 38 openchest dogs had measurements of percent segment length shortening (%SS) and velocity of segment length shortening either in midmyocardial or subepicardial and subendocardial ischemic segments before and after 60 min of left anterior descending coronary artery occlusion during 5 h of reperfusion; 10 addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A variety of animal models was employed and drugs were infused pre, peri and post ischaemia. Some studies showed dramatically positive results, whereas others showed no benefit [5, 6]. Results were often conflicting, confusing and inconsistent.…”
Section: Brief History Of Infarct Size Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of animal models was employed and drugs were infused pre, peri and post ischaemia. Some studies showed dramatically positive results, whereas others showed no benefit [5, 6]. Results were often conflicting, confusing and inconsistent.…”
Section: Brief History Of Infarct Size Limitationmentioning
confidence: 99%
“…Thirdly, surrogate end points of infarction such as enzyme derived infarct size or ST changes on the ECG, were imprecise. Even tetrazolium staining, that remains the ‘gold standard’ as a measure of infarct size, is prone to serious error and all results have to be interpreted with caution [5]. Consistency and reproducibility are vital when interpreting the significance of an unexpected isolated finding.…”
Section: Brief History Of Infarct Size Limitationmentioning
confidence: 99%
“…The extent of epicardial cyanosis corresponds to the area of epicardial ST segment elevation (15) and also to the extent of low blood flow as manifested by nonfluorescence along the epicardial surface of the heart when fluorescein is injected into the left atrium of dogs with coronary artery occlusions (26). The extent of epicardial cyanosis corresponds to the area of epicardial ST segment elevation (15) and also to the extent of low blood flow as manifested by nonfluorescence along the epicardial surface of the heart when fluorescein is injected into the left atrium of dogs with coronary artery occlusions (26).…”
mentioning
confidence: 99%